The acquisition of stop consonants by Danish two-year-old children - Jørgensen, John (Annual Report of the Institute of Phonetics University of Copenhagen, 1979)
This paper presents VOT data collected from four two-year-old Danish children. The results show that they differentiate the two categories - i.e. aspirated vs. unaspirated stops - in their production. The duration of aspiration in the unaspirated stops is found to be noticeably longer (the boundary between the two categories is at 50 ms) than what has been found in other investigations. An articulatory model accounting for the priority of a 0-30 ms VOT range for unaspirated stops is discussed and partly rejected.